Oral Mucosal Ulceration Caused by the Topical Application of a Concentrated Propolis Extract - Yuniardini Septorini Wimardhani; Anandina Irmagita Soegyanto (Case Reports in Dentistry)
Propolis is a resinous mixture that is collected by honey bees from tree buds, sap flow, and other botanical sources. Propolis has been extensively used in medicine, dentistry, and cosmetics; however, unwanted effects have been reported. This paper reports a case of oral mucosal burn in a 50-year-old patient, who used an overnight application of concentrated propolis to overcome a throbbing pain in the right upper posterior mucosa. The patient was otherwise healthy and was not receiving any medication. She presented with painful shallow multiple irregular ulcers measuring 0.3–1 cm in diameter that were located on the right buccal mucosa and hard palate mucosa, in addition to the gingival mucosa surrounding tooth 17. Propolis-induced oral mucosal burn was diagnosed. The ulcer cleared after the prescription of tetracycline mouthwash, accompanied with Doloneurobion. The patient was further treated with carbamazepine to address the persistent throbbing pain in the affected area, which was suspected to be trigeminal neuralgia. This report provides another alert to clinicians about the potential adverse effects of propolis use for the treatment of oral diseases, despite its natural origin.